MOLECULAR DOCKING STUDY TO TREAT FAMILIAL HYPERCHOLESTEROLEMIA USING NATURAL PHYTOCOMPOUNDS FROM INDIAN PANICUM MILIACEUM - KANAWADE, ANIKET; WANARASE, SHUBHAM (Innovare Journal of Medical Sciences, 2023)
Objectives: Lipoprotein disorders like Familial Hypercholesterolemia are crucial from the clinical point of view. In atherogenesis and the associated risk of atherosclerotic cardiovascular disease, lipoproteins are crucial. Therefore, to treat the disease, naturally active phytocompounds from an Indian millet Panicum miliaceum were used for molecular docking study and drug-likeness prediction along with absorption, distribution, metabolism, excretion (ADME) analysis. Methods: Proprotein convertase subtilin/kexin type 9 (PCSK9) decreases low-density lipoprotein (LDL) cholesterol levels in vivo by forming a complex with an LDL Receptor disruptor, according to a 3D structure retrieved from protein data bank (PDB). Plant phytocompound names and their structures were obtained from Indian medicinal plant, phytochemistry and therapeutics database and PDB, respectively. Docking was performed using two different docking software – PyRx. Results: Molecular docking study and drug-likeness prediction were carried out with the help of various computer-aided drug-designing tools and techniques. Five phytocompounds from P. miliaceum show prominent binding affinity toward PCSK9-disruptor complex, namely Diosgenin, Yamogenin, Miliacin, Germanicol, and beta-Amyrin are observed to possess drug-like properties that were confirmed through ADMET and drug likeliness studies. Conclusion: According to the present research, it has been concluded that Diosgenin, Yamogenin, Miliacin, Germanicol, and beta-Amyrin show specific interactions with the PCSK9-disruptor complex.